Factors that Influence the Weight Preeclampsia even Spinning Mother in Idaman Banjarbaru Hospital 2018 - Agria, Siti; Maslani, Noorhayati; Yuniarti, Yuniarti (JURNAL KEBIDANAN BESTARI, 2021)
Preeclampsia is a complication in pregnancy and childbirth obtained in increasing maternal-perinatal morbidity and mortality. Data in the maternity room in the Preeclampsia case ranked third in 2018 out of the top five cases. The study related to correlations of age, parity, Gemelli, assessment of hypertension, and the distance of maternal pregnancy with the incidence of Preeclampsia in Idaman Banjarbaru Hospital in 2018. Analytical survey research method by studying case-control using retrospective. Systematic Random Sampling. Secondary data. Analysis of data using the chi-square test of significance level α = 0.05 and 95% confidence level. The results showed that the number of deliveries with Preeclampsia was 163 respondents (33.3%), aged at risk 127 respondents (26%), unsafe parity 194 respondents (39.7%), Gemelli as many as 10 respondents (2%), hypertension research 44 (9%), and distance between unsafe pregnancies 57 (11.7%). Multivariate analysis showed factors related to the incidence of Preeclampsia were aged (OR: 3.721, CI: 2,438-5,678), parity (OR: 2,088, CI: 1,423-3,064), Gemelli (OR: 4,831, CI: 1,233- 18,935), looking for hypertension (OR: 13,382, CI: 5,813-30,805), pregnancy distance (OR: 1,739, CI: 1,184-2554). The conclusion is correlations between age, parity, Gemelli, assessment of hypertension, and the relationship of assessment to the incidence of Preeclampsia in Idaman Banjarbaru Hospital in 2018. Keywords: Age, Distance Of Pregnancy, Gamelli, History Of Hypertension, Parity, Preeclampsia.